THE COMPLEX IMPACT OF PEDAGOGICAL DIALOGUE ON STUDENTS' EMOTIONAL INTELLECTUALITY AND INTELLECTUAL DEVELOPMENT (Universal International Scientific Journal, 2026)
This thesis provides a comprehensive analysis of the impact of pedagogical communication on the emotional intelligence and intellectual development of students. In the modern education system, communication between a teacher and a student is considered not only a means of imparting knowledge, but also an important factor in personal development. The study reveals the importance of pedagogical communication in creating a psychological environment, forming independent thinking and emotional stability of students.
Keywords: pedagogical communication; emotional intelligence; intellectual development